Legal Criticism of the Effectiveness of Government Policies in Reducing the Rate of Early Marriage in Paleleh District, Buol Regency - Nurliska Y. Hentu; Lucyane Djafaar; Nopiana Mozin (SEAN Institute, 2026)
Early marriage remains a widespread social phenomenon in Indonesia, including in Paleleh District, Buol Regency, despite the increase in the minimum age regulation through Law No. 16 of 2019. This study aims to conduct a comprehensive legal critique of the effectiveness of government policies in reducing early marriage rates and identify obstacles encountered in the field. The method used is a descriptive qualitative approach, where data is collected through observation, documentation studies, and in-depth interviews with informants from government elements and early marriage perpetrators, which are then analyzed using the theory of legal effectiveness. The results of the study indicate that the policy has not been substantially effective because the number of underage marriages remains fluctuating and high, triggered by the exploitation of marriage dispensation loopholes and the practice of unregistered marriages. In addition, it was found that cultural factors of